The impact of asthma education grounded in virtual reality technology upon the quality of life of pediatric patients with bronchial asthma - Wang, Huijuan; Dong, Qing; Wang, Xiaowei (Frontiers in Pediatrics, 2025)
ObjectiveAsthma education stands as a pivotal element in the long - term management of asthma. This research endeavors to delve into the influence of virtual reality (VR) technology - based asthma education on the quality of life of children suffering from bronchial asthma.Methods81 children with bronchial asthma from the Sixth Hospital of Shijiazhuang (Aug 2023–Aug 2024) were randomly divided into VR (40 cases) and asthma education (41 cases) groups. The latter received conventional education, while the former used VR technology. C - ACT, CDI, SCARED, MMAS - 8, and PAQLQ were used for assessment. Surveys on help - seeking times and VR device satisfaction were also conducted.ResultsAfter and three months after the intervention, the VR group had higher C - ACT scores, more well - controlled asthma cases, lower CDI scores, fewer children with poor medication adherence, and higher MMAS - 8 scores than the asthma education group. Whether with severe or mild asthma, VR - based education improved C - ACT scores and the number of well - controlled cases. The VR group also had higher PAQLQ scores in symptoms, activity limitation, emotional function, and overall score. They accessed educational materials more often. 92.5% of parents/guardians were satisfied with VR devices and the program.ConclusionImplementing VR technology - based asthma education for children with bronchial asthma can enhance the asthma control status, effectively mitigate the children's negative emotions, augment medication adherence, and ultimately elevate their quality of life.